Estudo de fase clínica I utilizando membrana de quitosana dopada com hormônios derivados de plaquetas - Ferreira, Simone Da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Chronic wounds (CW are a constant challenge for pharmaceutical companies. The Blood Center of Botucatu develops products formulated 13 years ago from Fresh Plasma and platelets concentrate excess clinical practice. One of these products is well established and tested laminar platelet gel (Biogel/PG). Research in nursing identified opportunities for improvements to the Biogel/PG being proposed new wording: chitosan membrane enriched with platelet hormones (Quitogel). After preliminary studies have outlined the design of a phase I study in patients with CF using the Quitogel compared with Biogel/GP. This is a prospective, controlled clinical trial type, and aimed to compare the performance of the chitosan membrane doped with hormones versus Biogel/PG establishing the profile of patients seen. The past 24 months were served 135 new cases of CW, 45 male, mean age of 49.57 years and the time of open wound was 87.57 months. Females were 90 cases, with a mean age of 52.91 years and mean duration of open wound was 114.76 months. Regarding the type of ulcer, 81% were venous for women versus 64% for men. Chronic traumatic injuries (9%) were more prevalent in men, compared with 2% in women and diabetic wounds hit men (11%) more. Of marketed products most used by patients, include collagenase (16%), silver sulfadiazine (12%), fibrase ® (10%), papain (6%), Safgel ® (5%), 5% hydrogels. High rate of self-medication, a fact, compromising the outcome of the treatment of CW, where 33 (44.55%), was identified patients had reported having a prescribed product, but use the other 2 did not prescribed. Of these 135 patients, 27 of them participated in the study, a total of 31 lesions that were followed for 90 days. Comparison of the two products (Biogel/GP versus Quitogel), it was observed that in the preparation of doped chitosan membrane is easy storage (room temperature) and hydration with saline, gradually releases the hormones platelet does not favor ...

As Feridas Crônicas (FC) constituem um desafio constante para os laboratórios farmacêuticos. O Hemocentro de Botucatu desenvolve há 13 anos produtos formulados a partir do Plasma Fresco e do Concentrado de Plaquetas excedentes da prática clínica. Um destes produtos, bem estabelecidos e testados é o gel laminar de plaquetas (Biogel ou GP). Pesquisas na área de enfermagem identificaram oportunidades de melhorias para o Biogel sendo proposto nova formulação: membrana de quitosana enriquecida com hormônios plaquetários (Quitogel). Após estudos preliminares foi delineado o projeto de estudo de fase I, em pacientes portadores de FC utilizando o Quitogel comparando com o GP. Trata-se de um estudo prospectivo, do tipo ensaio clínico controlado, e teve como objetivo comparar o desempenho da membrana de quitosana dopada com hormônios plaquetários versus Gel de plaquetas estabelecendo o perfil de pacientes atendidos. Nos últimos 24 meses foram atendidos 135 novos casos de FC, sendo 45 do sexo masculino, com idade média de 49,57 anos e o tempo de ferida aberta foi de 87,57 meses. Do sexo feminino foram 90 casos, com média de idade de 52,91 anos e tempo médio de ferida aberta foi de 114,76 meses. Quanto ao tipo de úlcera, 81% foram venosas para mulheres contra 64% para homens. As lesões crônicas traumáticas (9%) foram mais prevalentes em homens, contra 2% em mulheres e as feridas diabéticas atingiram mais os homens (11%). Dos produtos comercializados mais usados pelos pacientes, destacam-se a colagenase (16%), sulfadiazina de prata (12%), fibrase® (10%), papaína (6%), Safgel®(5%), hidrogéis 5%. Foi identificado alto índice de automedicação, fato este, comprometedor do resultado do tratamento das FC, onde 33(44,55%), pacientes informavam ter um produto prescrito, mas usam voluntariamente outros 2 não prescritos. Destes 135 pacientes, participaram do estudo 27 deles, perfazendo um total de ...
Keywords: Quitosana; Ulcera varicosa - Tratamento; Curativos biológicos; Cicatrização de feridas; Biological dressings